Midwives’ Perception and Practice of Respectful Maternity Care During Pregnancy and Childbirth in Selected Health Facilities in Cross River State, Nigeria (African Journal of Biomedical Research, 2022)
Respectful maternity care is a care organized for and provided to all women in a manner that maintains their dignity, privacy and confidentiality, ensures freedom from harm and mistreatment and enables informed choice and continuous support during labour and childbirth. This study examines midwives’ perception and practice of respectful maternity care during labour and childbirth. The study adopted a correlational design. The study setting was Cross River State and the sites for the study were the University of Calabar Teaching Hospital and General Hospital Calabar.  Two different populations were used. Midwives total was population (144 midwives). Data were collected using a structured self-explanatory questionnaire (with test-retest r of 0.86) and an observational checklist. Data were analysed using SPSS 25 and presented using descriptive and inferential statistics, hypotheses were tested using population t-test and Pearson product moment correlation coefficient. Findings from the study revealed midwives had a moderate (6.6/10) level of knowledge of respectful maternity care and a positive perception towards respectful maternity care. The practise of respectful maternity care was significantly high (p0.05). Midwives should seek to understand the views of women and their families on issues relating to their care, this will contribute immensely to the development and implementation of appropriate intervention.